Latihan Pernapasan dengan Metode Buteyko Meningkatkan Nilai Force Expiratory Volume In 1 Second (%Fev1) Penderita Asma Dewasa Derajat Persisten Sedang - Denny Agustiningsih, Abdul Kafi, Achmad Djunaidi (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: Breathing exercises are frequently recommended as an adjunctive treatment for asthma. Breathing exercise for asthma that is recommended in Indonesia is Senam Asma Indonesia, which has a session of aerobic exercise. In Russia and Australia Buteyko method is practiced as a simple exercise for respiration. Principally, the technique of Buteyko is different from other respiration methods.Objective: The aim of this study is to know if the effect of Buteyko method could increase lung function of adult asthmatic patient better than Senam Asma Indonesia.Methods: Design of this study is field experiment with pretest and posttest of the lung function test (FVC, %FVC, FEV1 and %FEV1). The subjects divided into three groups, the group I, given exercise with the Buteyko method, group II given exercise with Senam Asma Indonesia and the group III without any exercise. The exercise was given for 12 weeks. The lung function test was done at the end of every month for all groups.Result: %FEV1 for Buteyko’s group increased significantly but other parameters didn’t.Conclusion: Breathing exercises with Buteyko and Senam Asma Indonesia both could decrease the airway resistance in asthmatic patient, but could not improve the vital capacity of the lung.Keywords: asthma; buteyko method, senam asma Indonesia, lung function test